Model pembangunan pertanian desa palur - Kusuma, Clarashinta; Nurdiana, Defia Wahyu; Fajri, Habiburrosyad Al; Aji, Ilham Adhyaksa Seno; Linggi, Nidya Sukmawati; Antriyandarti, Ernoiz (Institute for Advanced Science, Social, and Sustainable Future (IASSSF), 2024)
Agricultural development plays a crucial role in Indonesia's economic growth, particularly because the majority of its population relies on the agricultural sector. However, this sector faces several challenges, such as structural, institutional, and technological issues. To address these challenges, Palur Village, Mojolaban District, Sukoharjo Regency, is the focus of this study. Through descriptive analysis method, primary and secondary data were obtained through interviews, observations, and recordings. Palur Village's potential includes significant agricultural land and productive human resources, but it faces issues of resource allocation and a lack of interest in agriculture. Structural transformation indicates a shift from the agricultural sector to the industrial or service sectors, but with low incomes. Institutional transformation, on one hand, shows continuity in existing institutional functions without major changes, but the success and changes occurring in local financial institutions indicate the need for further transformation. Technology transfer, especially through the use of modern tools and technology in agriculture, has brought positive changes but still faces challenges in adopting innovations. Based on this analysis, the appropriate agricultural development model for Palur Village is The Diffusion Model, which emphasizes education and the dissemination of technology to enhance productivity and address the challenges faced by local farmers. With proper implementation, this model can serve as a foundation for improving welfare and economic growth in Palur Village and similar areas.